Image-based data mining applies to data collected from children. (July 2022) - Wilson, Lydia J.; Bryce-Atkinson, Abigail; Green, Andrew; Li, Yimei; Merchant, Thomas E.; van Herk, Marcel; Vasquez Osorio, Eliana; Faught, Austin M.; Aznar, Marianne C.
Graphical abstract: Highlights: The applicability of the complete IBDM workflow to pediatric data was assessed for the first time. IBDM is robustly applicable to pediatric data. IBDM reliably identifies systematic dose differences as small as 1%. IBDM performance is sensitive to characteristics of the dose and incidence rate. Abstract: Purpose: Image-based data mining (IBDM) is a novel voxel-based method for analyzing radiation dose responses that has been successfully applied in adult data. Because anatomic variability and side effects of interest differ for children compared to adults, we investigated the feasibility of IBDM for pediatric analyses. Methods: We tested IBDM with CT images and dose distributions collected from 167 children (aged 10 months to 20 years) who received proton radiotherapy for primary brain tumors. We used data from four reference patients to assess IBDM sensitivity to reference selection. We quantified spatial-normalization accuracy via contour distances and deviations of the centers-of-mass of brain substructures. We performed dose comparisons with simplified and modified clinical dose distributions with a simulated effect, assessing their accuracy via sensitivity, positive predictive value (PPV) and Dice similarity coefficient (DSC). Results: Spatial normalizations and dose comparisons were insensitive to reference selection. Normalization discrepancies were small (average contour distance < 2.5 mm, average center-of-mass deviation < 6 mm). Dose comparisons identified differences (p < 0.01) in 81% of simplified and all modified clinical dose distributions. The DSCs for simplified doses were high (peak frequency magnitudes of 0.9–1.0). However, the PPVs and DSCs were low (maximum 0.3 and 0.4, respectively) in the modified clinical tests. Conclusions: IBDM is feasible for childhood late-effects research. Our findings may inform cohort selection in future studies of pediatric radiotherapy dose responses and facilitate treatment planning to reduce treatment-related toxicities and improve quality of life among childhood cancer survivors.